Systematic Reduction of the Detailed Kinetic Mechanism for the Combustion of n-Butane - Chunhui Liu; Zhengxing Zuo; Huihua Feng (Journal of Chemistry)
A systematic approach for mechanism reduction was demonstrated to generate a skeletal and reduced mechanism for the oxidation of n-butane. First, a skeletal mechanism, including 89 species and 440 elementary reactions, was derived from a 230-species detailed mechanism using path flux analysis (PFA). Then, the unimportant reactions were eliminated using the importance index defined in computational singular perturbation (CSP), resulting in a skeletal mechanism consisting of 89 species and 298 elementary reactions. Finally, 20 global quasi-steady-state species were identified using a CSP-based time-scale analysis, leading to a 69-species reduced mechanism. Validation of the 89-species skeletal and 69-species reduced mechanisms showed good agreement with the detailed mechanism for both the ignition delay time and the distribution of species concentration over a wide range of simulation conditions.